Synthesis of N-Trifluoromethyl Thiocarbamates and Ureas from 3-Aminopyridine-Derived Carbamates - He, Xingjin; Deng, Linbei; You, Ying; Lai, Yongxing; Liu, Jianbo (Synthesis, 2024)
The synthesis of N-trifluoromethyl thiocarbamates and ureas from 3-pyridyl isothiocyanates via the nucleophilic substitution reaction of perfluorophenyl pyridin-3-yl(trifluoromethyl)carbamate is described. Recently, Schoenebeck’s group reported a straightforward method to access N-trifluoromethyl analogues of amides and related carbonyl compounds. However, N-trifluoromethyl thiocarbamates and ureas derived from pyridine-containing amines remain a synthetic challenge. In this paper, the strategy relies on the operationally simple preparation of perfluorophenyl pyridin-3-yl(trifluoromethyl)carbamates, which can smoothly undergo nucleophilic substitution reactions with thiophenol, sodium mercaptide, and amine. Various functional groups such as amide, halogen, ether, and ester were tolerated under these reaction conditions. Notably, alkylamine structures containing pyridine heterocyclic rings are also compatible to access N-trifluoromethyl thiocarbamates.
Keywords: N-trifluoromethyl thiocarbamate; N-trifluoromethyl urea; pyridine-containing amine; alkylamine; nucleophilic substitution